Adding exogenous protein relieves the toxicity of nanoparticles to anammox granular sludge by adsorption and the formation of eco-coronas. Issue 5 (30th March 2022) - Ma, Wen-Jie; Wang, Xin; Zhang, Jiang-Tao; Guo, Jie-Yun; Lin, Yan-Xu; Yao, Yu-Xi; Li, Gui-Feng; Cheng, Ya-Fei; Fan, Nian-Si; Jin, Ren-Cun
Abstract : MgO nanoparticles (NPs) are widely used in bactericides, fuel cells and electronic materials and are frequently detected in aquatic environments. Abstract : MgO nanoparticles (NPs) are widely used in bactericides, fuel cells and electronic materials and are frequently detected in aquatic environments. Anaerobic ammonium oxidation (anammox) is a highly efficient and economical autotrophic nitrogen removal process. To date, the effects of MgO NPs on anammox granular sludge have remained unknown. This work systematically evaluated the short- and long-term effects of MgO NPs on anammox process performance and explored an effective strategy to relieve stress. The half maximal inhibitory concentration (IC50 ) of MgO NPs to anammox granular sludge was 69.5 mg L −1 . During the long-term experiment, the anammox process experienced a reduction in nitrogen removal ability under the stress of 50.0 mg L −1 MgO NPs. Moreover, the enzymatic activity and synthesis of heme c significantly decreased. Adding 40.0 mg L −1 bull serum albumin (BSA) effectively relieved the stress caused by 50.0 mg L −1 MgO NPs, and the anammox activity recovered to 97.0% of the original level. Multiple spectral analyses verified the adsorption of MgO NPs by BSA. Furthermore, the formation of an eco-corona was observed by transmission electron microscopy, which also contributed to decreasing the biotoxicity of the MgO NPs. The results of this study provide guidance for treating NP-containing wastewater during the anammox process.